Indonesia : Towards Democracy - Abdullah, Taufik (Book collections on Project MUSE., 2009)
This book traces the beginning of the process of nation-formation, the struggle for independence, the hopeful beginning of the new nation-state of Indonesia only to be followed by hard and difficult ways to remain true to the ideals of independence. In the process Indonesia with its sprawling archipelago and its multi-ethnic and multi-religious nation has to undergo various types of crisis and internal conflicts, but the ideals that have been nurtured since the beginning when a new nation began to be visualized remain intact. Some changes in the interpretation may have taken place and some deviations here and there can be noticed but the literal meaning of the ideals continues to be the guiding light. In short this is a history of a nation in the continuing effort to retain the ideals of its existence.--